Simultaneous growth promoting and managing bacterial wilt of tomato through Bacillus amyloliquefaciens - YADAV, DHANANJAY KUMAR; SINGH, DINESH; KUMAR, NARENDRA (The Indian Journal of Agricultural Sciences, 2019)
Bacterial wilt disease, caused by Ralstonia solanacearum (Smith) Yabuuchi has become a severe problem in tomato crops and no satisfactory control methods are currently available to reduce damage caused by the disease. For biological control of the disease, plant growth promoting rhizobacteria (PGPR) isolates particularly from Bacillus spp. may be considered as a promising strategy for managing the disease. Thirty nine isolates of Bacillus amyloliquefaciens, isolated from rhizospheric soil of solanaceous crops were characterized antagonistic and plant growth promoting activities in vitro conditions. The isolate UKTBA-8 of B. amyloliquefaciens was found best among all other isolates, that inhibited maximum growth of R. solanacearum under in vitro conditions and formed inhibition zone of 3.96 cm2 followed by HPTBA-1 (3.3 cm2) and MPBA-6 (2.56 cm2). UKTBA-8 solubilized the highest phosphorus (81.59 μg/ ml) produced maximum siderophores to form orange yellow halo (1.96 cm diameter) and indole acetic acid ranging from 41.25–97.41 μg/ml under in vitro conditions. Biocontrol efficacy and plant growth ability of best six bacterial antagonists, viz. HPTBA-1, MPBA-6, JHBA-6, ORTBA-1, KCBA-4 and UKTBA-8 were evaluated to control bacterial wilt disease of tomato cv. Pusa Ruby at National Phytotran Facility, IARI, New Delhi. B. amyloliquefaciens UKTBA-8 treated plants showed least wilt incidence (12.23%) with maximum biocontrol efficacy (83.36%) after 30 days of inoculation.